2018
DOI: 10.25002/tji.2018.866
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Extract Suppresses B Cell Activation Through TLR3/TLR4 in High Fat-High Fructose Diet Mice

Abstract: Introduction: The relationship between B cells and Toll-like Receptors (TLRs) under high fat−high fructose diet (HFFD) is still poorly understood. Isoflavone content from soybean can be modified by using biotic and abiotic elicitors to synthesize glyceollin. Glyceollin has gained much interest in recent past year due to its beneficial effects on health. The study aimed to examine the ameliorative effect of elicited soybean extract (ESE) on B cells profile in HFFD mice. Material and Methods: Twenty-eight female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Atho’illah et al. demonstrated that ESE decline TLR3 and TLR4 in B cells of HFFD mice [ 24 ]. Another phytoalexin contains in grape, resveratrol, inhibits TBK1, and RIP1 in TRIF complex [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atho’illah et al. demonstrated that ESE decline TLR3 and TLR4 in B cells of HFFD mice [ 24 ]. Another phytoalexin contains in grape, resveratrol, inhibits TBK1, and RIP1 in TRIF complex [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The spleen samples were taken, washed twice with sterile PBS, and smashed into a single-cell suspension. A single-cell suspension of the spleen has been prepared as per routine laboratory procedures [ 24 ]. Subsequent splenic lymphocytes were centrifuged at 2500 rpm for 5 min at 10 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Single-cell suspensions then added with PBS until reached 10 mL and centrifuged at 2500 rpm for 5 min at 10°C. The supernatant then discarded and the pellet was homogenized with 1 mL PBS [20]. Homogenates then divided into several 1.5 mL tubes according to the staining used then centrifuged at 2500 rpm for 5 min at 10°C.…”
Section: Methodsmentioning
confidence: 99%
“…The suspension was then put into a 15 mL polypropylene centrifuge tube. (20) The lymphocyte density was calculated under the light microscope using a hemocytometer and trypan blue staining. (21) The number of lymphocytes was counted in 5 large squares of the hemocytometer.…”
Section: Measurement Of Lymphocyte Densitymentioning
confidence: 99%